(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article describes the features of professional ethics of accountants, auditors and tax officers as an important condition for achieving the better productivity. The essence of the concept of professional ethics is stated. Professional ethics is a code of rules that determine the behavior of a specialist in the performance of professional duties and guarantee compliance with moral norms within the current legislation. The basic principles of ethics of professional accountants are clarified. The algorithm of identification and assessment of threats to the observance of basic principles and application of precautionary measures is determined. It is established that the observance of professional ethics by an accountant, auditor and tax officer is one of the most important factors of clients’ trust in the results of their work.